International Tax Avoidance Practice in ASEAN-4 Multinational Company - Masri, Indah (Fakultas Pendidikan Ekonomi dan Bisnis, 2021)
This study held an evaluation on the role of Tax Risk Management and Government Governance in accordance with international tax practice with tax avoidance. This study uses panel data from year 2010 to 2016 of multinational companies in 4 ASEAN countries namely Indonesia, Malaysia, Singapore, and Philipines as samples. The study result proves that Tax Risk Management and Government Governance successfully decrease international tax avoidance practice in multinational companies in ASEAN especially on Thin capitalization and multinational practice. It means the company performing internal supervision by having task risk management and a better government governance can minimize the negative impact of international tax avoidance practice. Meanwhile, tax havens practice is not significantly influenced since some samples of this study are multinational companies in tax haven country namely, Singapore and Labuan Malaysia. Therefore, the role of task risk management and government governance is not too significant.Â Â